2014
DOI: 10.1179/1362171814y.0000000235
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and mechanical properties of friction spot welded Alclad 7B04-T74 aluminium alloy

Abstract: Two millimetre thick Alclad 7B04-T74 aluminium alloy was friction spot welded at different tool rotation speeds. The weld formation, Alclad redistribution, microstructures and mechanical properties of the joints were investigated. The results indicate that inappropriate tool rotation speeds can give rise to weld defects, such as annular groove, void and surface concavity. After welding, the original surface Alclad is redistributed as a U shaped Alclad layer in the weld. When the tool rotation speed is relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…According to the previous studies on FSpW of 7B04-T74 aluminum alloy by the present authors, the optimal welding parameters were tool rotation speed of 1500 rpm, sleeve motion speed of 1 mm/s, and sleeve plunge depth of 3 mm. In addition, a surface indentation with 0.15 mm depth was applied, which had been proved to be necessary for a good weld formation by the present authors [2,3]. Therefore, such welding parameters mentioned above were chosen as the welding parameters applied in this study.…”
Section: Materials and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous studies on FSpW of 7B04-T74 aluminum alloy by the present authors, the optimal welding parameters were tool rotation speed of 1500 rpm, sleeve motion speed of 1 mm/s, and sleeve plunge depth of 3 mm. In addition, a surface indentation with 0.15 mm depth was applied, which had been proved to be necessary for a good weld formation by the present authors [2,3]. Therefore, such welding parameters mentioned above were chosen as the welding parameters applied in this study.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…Friction spot welding (FSpW) is a new solid state joining technique, which is derived from the conventional friction stir welding (FSW) process [1,2]. Comparing with the conventional friction stir spot welding (FSSW), there is no keyhole left in the FSpW joint, so higher mechanical properties can be obtained and the corrosion near the bottom of the keyhole can be avoided [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Since its invention, refill FSSW has been used for joining similar metals or materials [6][7][8][9][10] as well as joining dissimilar materials. [11][12][13][14] HZG proved that refill FSSW creates joints with superior mechanical properties to similar processes.…”
mentioning
confidence: 99%
“…The employed tool rotation speed, sleeve motion speed, and sleeve plunge depth were 1500 rpm, 1 mm/s, and 3 mm respectively. This set of parameters had been proved to be optimized by the present authors [10]. Previous study conducted by the present authors indicated that a part of plastic material would overflow out from the welding region in the RFSSW process, the left material was not enough to refill the welding spot.…”
Section: Materials and Experimentsmentioning
confidence: 74%
“…Only a few relative studies have been conducted. Zhao et al [10] studied the microstructures of RFSSW joints of 7B04-T74 aluminum alloy at different tool rotation speeds. They found that the grains in the outer stir zone were equiaxed, and the grains in the inner stir zone were elongated and coarsened.…”
Section: Introductionmentioning
confidence: 99%